The idea basis of a Marxist research programme, or How to remain a Marxist - Mikhailouski, Vadzim S. (Journal of the Belarusian State University. Sociology, 2023)
Marxism never stood still and developed as a research programme – a unit of scientific knowledge, which is a set of interchangeable concepts connected by a single ideological foundation. The Marxist research programme consists of three parts: classical, party and neo-Marxist. The heuristic of the programmatic development of Marxist thought is made up of three strengths of all Marxist trends: classical funding, a conservative party approach, and neo-Marxist freedom of interpretation. The question of the ideological basis of all Marxism remains open. The article defends the position that the programme foundation of Marxism should be minimal in order to maximally include all previous and future research into the Marxist research programme (quantitative criterion). It is concluded that despite the extensive, contradictory and competing research heritage, all Marxist knowledge invariably followed the class-dialectical approach (qualitative criterion). Marxism in the minimum required dimension defends only two main ideas: the modern world is the reproduction of class-power confrontation, and not public management technologies; the modern world is a transient stage in the development of mankind, and not a second nature.